2018
DOI: 10.1186/s12882-018-0940-3
|View full text |Cite
|
Sign up to set email alerts
|

IP3R-Grp75-VDAC1-MCU calcium regulation axis antagonists protect podocytes from apoptosis and decrease proteinuria in an Adriamycin nephropathy rat model

Abstract: BackgroundThe mechanism of podocyte apoptosis is not fully understood. In addition, the role of the inositol 1,4,5-triphosphate receptor (IP3R)/glucose-regulated protein 75 (Grp75)/voltage-dependent anion channel 1 (VDAC1)/mitochondrial calcium uniporter (MCU) calcium regulation axis, which is located at sites of endoplasmic reticulum (ER) mitochondria coupling, in the mechanism of podocyte apoptosis is unclear. This study aimed to understand the roles of this axis in podocyte apoptosis and explore potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 20 publications
2
86
0
Order By: Relevance
“…Antagonists of this calcium axis were shown to prevent podocyte apoptosis [2]. We also found that the MCU inhibitor ruthenium red (RR) significantly improved proteinuria and podocyte foot process effacement in ADR-induced nephropathy rats [2]. Based on the above findings, we hypothesized that the IP 3 R-Grp75-VDAC1-MCU calcium axis is involved in the development of proteinuria.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Antagonists of this calcium axis were shown to prevent podocyte apoptosis [2]. We also found that the MCU inhibitor ruthenium red (RR) significantly improved proteinuria and podocyte foot process effacement in ADR-induced nephropathy rats [2]. Based on the above findings, we hypothesized that the IP 3 R-Grp75-VDAC1-MCU calcium axis is involved in the development of proteinuria.…”
Section: Introductionmentioning
confidence: 91%
“…All protocols were approved by the Institutional Animal Care and Use Committee of Peking University First Hospital (number: 11400700229305). This study used a previously reported model [2]. ADR (D1515, Sigma, Santa Clara, California, USA) was successfully used to induce a nephropathy model in Sprague-Dawley rats (Beijing Vital River Laboratory Animal Technology Co. Ltd.) as previously 4 reported.…”
Section: Adr Nephropathy Rat Model Development and Mcu Inhibitor Treamentioning
confidence: 99%
See 3 more Smart Citations